PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK SMP KELAS VIII DENGAN MODEL KOOPERATIF TIPE STAD - Mila Amelia; Nurjanah Nurjanah (UJMES (Uninus Journal of Mathematics Education and Science), 2020)
This research is motivated by the low ability of students' mathematical understanding in mathematics learning. One alternative to improve students' mathematical understanding skills is the STAD type cooperative learning model (Student Teams Achievement Division). The purpose of this study was to determine the increase in the ability of mathematical understanding of students who gained learning with the STAD model and the students who received learning with the PBL (Problem Based Learning). The research method used was the quasi-experimental method with the Nonequivalent Pretest-Posttest Control Group Design. This research was conducted in one of the Public Middle Schools in Bandung. The population were all eighth grade students, with the sample being students of class VIII A as the experimental class and class VIII C as the control class. The instruments used were in the form of tests of mathematical comprehension abilities, and educator observation sheets. Based on the results of the t-test analysis, it was concluded that the increase in the ability of mathematical understanding of students who obtained learning with the STAD was higher than the students who obtained learning with the PBL profiles of students who obtained learning with the STAD included in the high category in mathematics learning.